Biomass Yield of Irrigated/Rain-fed Oat and Vetch Fodder - International Livestock Research Institute (International Livestock Research Institute, 2014)
Biomass yield is taken on seasonal basis and the effect of supplementing the fodder to livestock in terms of weight gain/milk yield is documented using different tools following the growth and harvest of the fodder. To learn more about this dataset, please visit the ILRI Datasets Portal http://data.ilri.org/portal/dataset/irr_rain_fodder